Sistem Informasi Penerimaan dan Pengeluaran Kas pada TK Alfaronizam - Fadhil, Fadhil Yudistianto; Suarna, Nana; Rahaningsih, Nining (LPPM UNIKA Santo Thomas Medan, 2023)
Information systems have an important role in educational institutions such as kindergartens, one of which is the cash receipt and expenditure information system. Alfaronizam Kindergarten has a problem in recording cash receipts and disbursements which are still manual. This causes time inefficiency and is prone to errors in recording. Therefore, a solution is needed to facilitate the recording process and increase time efficiency. The purpose of writing this report is to produce a website-based cash receipt and expenditure information system that is considered appropriate to overcome these problems. The data collection method used in designing this system is by conducting observations, documentation, literature studies, and interviews with the principal and treasurer of Alfaronizam Kindergarten. After the data has been obtained, the data is processed and then continued with the system development process using the waterfall method which has several stages, namely analysis, design, implementation, system testing and maintenance. Made with the text editor sublime text 3 with the PHP programming language, and using the local web server XAMPP. The expected results in the cash receipts and disbursements system developed can help overcome the problem of manual recording and increase time efficiency in recording.